PEMBERDAYAAN EKONOMI MASYARAKAT DESA MELALUI PROGRAM PINJAMAN BERGULIR PNPM MANDIRI PERKOTAAN (DI DESA GAMBIRAN DAN DESA MANCILAN DI KECAMATAN MOJOAGUNG KABUPATEN JOMBANG JAWA TIMUR TAHUN 2014-2016) - cindy martha devi; Kushandajani .; nunik retno herawati (Journal of Politic and Government Studies, 2017)
one of the programs launced by PNMP Mandiri Perkotaan which is a part of BLM (Community Direct Assistance) is a Revolving Loan aimed to communities and community groups that own small and medium enterprises as well as newly started businesses and require loans or assistance for business capital at interest affordable. One of the villages in Mojoagung sub-district, Jombang regency of East Java, which implements revolving loan is Gambiran and Mancilan Village, but in both villages there is a difference of sustainability level and success of the Revolving Loan from 2014 to 2016.The research method used in this research is qualitative approach with data collection technique that is data analysis, observation and interview. The informants in this study were Head of Gambiran Village and Head of Mancilan Village, UPK Gambiran Village and UPK Mancilan Village, Economic Facilitator of Gambiran and Mancilan Village, Gambiran and Mancilan Village Community which uses the revolving loan.The result of the research shows that there is a difference of sustainability level and success of the Revolving Loans in Gambiran and Mancilan Village. If it is seen from the analysis of indicators of sustainability and success, the Revolving Loans in Gambiran Village are categorized as continuous and successful while the Revolving Loans in Mancilan Village are categorized as continuous but not successful.Recommendations that can be made to the Government and UPK Mancilan Village is to improve coordination with facilitators and other Community Leaders in the process of socializing and billing the Revolving Loans to the community in order to avoid an installment of credit jam.Keywords: Revolving Loans, PNPM Mandiri Perkotaan, Jombang Regency